Hand Eczema in Nurses in COVID-19 Treatment Room: Frequency of Handwashing, Hand Sanitizer, Moisturizer, and Duration of Latex Gloves Use - Rosmarwati, Ervina; Widhiati, Suci; Novriana, Dita Eka; Rahma, Alfina; Kariosentono, Harijono; Irawanto, Muhammad Eko; Kusumawardani, Arie; Ellistasari, Endra Yustin; Oktavriana, Triasari (Faculty of Medicine, Universitas Airlangga, 2022)
Background: The COVID-19 pandemic causes health workers to use level 2 and level 3 personal protective equipment. Hand washing and the use of latex gloves are important in limiting the spread of COVID-19, but they can potentially induce hand eczema and skin pH disturbance if used too frequently. Purpose: Determine the correlation between the frequency of handwashing and duration of using hand sanitizer and moisturizer as well as skin pH level on the incidence of hand eczema in nurses in the COVID-19 treatment room at RSUD Dr. Moewardi Surakarta. Methods: This cross-sectional study was conducted in the COVID-19 treatment room at RSUD Dr. Moewardi Surakarta with 90 nurses as subjects. A validated questionnaire carried out the frequency of handwashing, hand sanitizer, moisturizer, duration of using latex gloves, and hand eczema complaints. The subject's pH assessment was conducted after 4-5 hours in the COVID-19 treatment room. Data were analyzed bivariately with a Spearman rank correlation test. Result: There was a significant correlation with the incidence of hand eczema with the frequency of handwashing with soap (r=0.305 and p=0.003) and the duration of using latex gloves (r=0.328 and p=0.002) with a weak category correlation (r=0.200-0.399). The frequency of using hand sanitizer, moisturizer, and skin pH did not correlate with the incidence of hand eczema. Conclusion: Frequency of handwashing and the duration of using latex gloves correlated with the incidence of hand eczema, meanwhile frequency of using hand sanitizer, using moisturizer, and skin pH didn't correlate with the incidence of hand eczema.